2018
DOI: 10.1016/j.neubiorev.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammation in core features of depression: Insights from paradigms using exogenously-induced inflammation

Abstract: A wealth of evidence has implicated inflammation in the development of depression. Yet, the heterogeneous nature of depression has impeded efforts to understand, prevent, and treat the disease. The purpose of this integrative review is to summarize the connections between inflammation and established core features of depression that exhibit more homogeneity than the syndrome itself: exaggerated reactivity to negative information, altered reward processing, decreased cognitive control, and somatic syndrome. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 245 publications
(368 reference statements)
7
122
0
1
Order By: Relevance
“…Indeed, experimental animal models have shown that vulnerability to the behavioral effects of stress are linked to greater permeability in the BBB (Menard et al, ). Through these and other mechanisms, neuroinflammation during critical phases of development may alter functional circuits in the brain (Ganguly & Brenhouse, ) and have profound implications for several neurotransmitters, including glutamate, serotonin, and dopamine (Dooley et al, ; Miller, Haroon, Raison, & Felger, ). Of course, these mechanisms are not mutually exclusive, and more translational research is needed to better characterize the development of functional circuits in the context of these developmental neuroimmune processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, experimental animal models have shown that vulnerability to the behavioral effects of stress are linked to greater permeability in the BBB (Menard et al, ). Through these and other mechanisms, neuroinflammation during critical phases of development may alter functional circuits in the brain (Ganguly & Brenhouse, ) and have profound implications for several neurotransmitters, including glutamate, serotonin, and dopamine (Dooley et al, ; Miller, Haroon, Raison, & Felger, ). Of course, these mechanisms are not mutually exclusive, and more translational research is needed to better characterize the development of functional circuits in the context of these developmental neuroimmune processes.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of indices of inflammatory signaling that are more sensitive than IL‐6 alone, including multiplex assays that measure multiple circulating inflammatory proteins, expression of genes associated with the production and regulation of inflammation, and expression of RNA transcription factors that are linked to inflammation (Cole, ; Slavich & Cole, ). Similarly, psychological sensitivity to inflammatory signaling could be manifested at many levels of analysis, such as through structural and functional connectivity of neural circuits that govern mood, or through performance on behavioral and neuropsychological tasks (See Dooley et al, for review). Furthermore, our interpretations of psychological sensitivity to the influenza vaccine are limited by the imbalance in sampling frequency between our mood and inflammatory measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers have now proposed that proinflammatory cytokines may play a role in the pathogenesis of depression (Capuron & Miller, ; Dantzer, O'Connor, Freund, Johnson, & Kelley, ; Dooley et al, ; Miller & Raison, ; Raison & Miller, ). Consistent with this hypothesis, research finds that patients with major depressive disorder have higher levels of inflammation in their peripheral blood and cerebrospinal fluid than do healthy controls (Berk et al, ; Raison & Miller, ).…”
Section: Inflammation Impacts How We Think Feel and Behavementioning
confidence: 99%